Accelerating growth and structural transformation: Ghana's options for reaching middle-income country status - Breisinger, Clemens; Diao, Xinshen; Thurlow, James; Yu, Bingxin; Kolavalli, Shashidhara (International Food Policy Research Institute, 2008)
Ghana is an emerging success story in Africa and in a couple of years will become the first African country to achieve the first Millennium Development Goal of halving its national poverty rate. The government of Ghana has therefore extended its development vision and recently declared the goal of reaching middle-income-country (MIC) status by 2015. To analyze possible pathways and implications of achieving MIC status, this paper examines other countries' experiences on their way to becoming MICs and emphasizes the important role of growth acceleration, export diversification, and economic structural change in the transformation process. The paper further analyzes Ghana?s growth options and their structural implications using a dynamic computable general equilibrium model recently developed for Ghana. The results of the model simulation suggest that Ghana?s annual GDP growth rate must accelerate from the recent 5.5 percent to 7.6 percent to achieve MIC status by 2015. Unlike in other countries, agriculture in Ghana is likely to remain the mainstay of growth and export earnings, while the role of manufacturing growth in achieving MIC status may be constrained by the manufacturing sector's dependency on agricultural inputs and small size. Services may not become the prime mover of accelerated growth, but improved efficiency in trade, transport, and business services will be a key for growth acceleration in other sectors.